THE IDIOMS AND CULTURE-SPCIFIC ITEMS TRANSLATION STRATEGY FOR A CLASSIC NOVEL - Inayah Ahyana Rohmawati; Esti Junining; Pratnyawati Nuridi Suwarso (Journey: Journal of English Language and Pedagogy, 2022)
A translator must have a thorough grasp of a language and its culture in order to determine the most appropriate interpretation while being true to the culture's intent. They must understand the translation technique and category to maintain consistency while translating cultural texts such as idioms and culture-specific items. This study explored translation procedures for idioms and culture-specific items, as well as their categories, in light of these considerations. The researcher did a descriptive qualitative study utilizing two instruments from Lucy M. Montgomery's original novel "Anne's House of Dreams," which was first published in 1917 and had 275 pages. Meanwhile, Maria M. Lubis released a 275-page Indonesian translation in 1998. According to the findings, there were 146 data points for idioms and 26 data points for culture-specific things. The most common translation approach utilized was Translation by Paraphrase, and the least common was Translation by Omission, according to the initial statistics on idioms. Meanwhile, the second set of data on Culture-specific Items revealed that Transfer was the most regularly utilized translation approach, while Deletion was the least. Finally, the most often used category for classification was Ecology. Overall, we believe that this study will aid readers in comprehending translation.